ANALISIS SIMPANG TAK BERSINYAL PADA SIMPANG PUSAT PERTOKOAN PANCOR (PTC) LOMBOK TIMUR - Eti Kurniati; Abdul Muid; Hermansyah (Jurnal Informatika Teknologi dan Sains, 2022)
The development of transportation has an impact on increasing the movement of people, goods and services. Improving transportation facilities and infrastructure is also highly demanded. This research is research with observation or current events or phenomena that exist today or that occurred in the past (Sugiono, 2016). In this study, it aims to find the value of the degree of saturation at the intended research location. Even this study uses MKJI 1997 rules to analyze data that has been surveyed. From the results of the analysis carried out, it can be seen that the volume of the PTC East Lombok intersection of four currents is 2713 smp/hour, the capacity is 2989 smp/hour with a degree of saturation reaching 0.90. Meanwhile, the delay is 15.43 smp/sec with an upper limit queuing opportunity of 64.11% and a lower limit of 32.50%. Based on the value of the degree of saturation above 0.75, it is necessary to install a signaling device or Traffic Light. The intersection delay value is 15.43 seconds/smp